2013
DOI: 10.5424/sjar/2013113-3536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genotype, Cr(III) and Cr(VI) on plant growth and micronutrient status in Silene vulgaris (Moench)

Abstract: Chromium released into the environment from industrial activities has become an important environmental concern. Silene vulgaris has been proven to be tolerant to many heavy metals, so it is considered an interesting species in the revegetation and restoration of polluted soils, but no information is available about its response to Cr. The objective of this work was to study uptake and influence on plant growth of Cr(III) and Cr(VI) in six genotypes (four hermaphrodites and two females) of S. vulgaris from dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…In this study, high concentration of Cr level (120 µM) resulted in decreases in root, as well as shoot length and biomass of seedlings of both the cultivars (Figure 3), and similar Cr toxicity effects have been observed in Cicer arietinum (Singh et al, 2020) and Vigna radiate (Jabeen et al, 2016). These results indicate a potential interaction of Cr ions with some essential mineral nutrients in soil, and, in turn, reduces their uptake by plants (del Real et al, 2013). The Cr stress-induced decrease in root length in the present study could be because of Cr accumulation in root cells or due to damage of root tip cells, whereas the decrease in shoot length may be due to ultrastructural damage in leaf mesophyll cells, which ultimately results in decreased shoot development.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, high concentration of Cr level (120 µM) resulted in decreases in root, as well as shoot length and biomass of seedlings of both the cultivars (Figure 3), and similar Cr toxicity effects have been observed in Cicer arietinum (Singh et al, 2020) and Vigna radiate (Jabeen et al, 2016). These results indicate a potential interaction of Cr ions with some essential mineral nutrients in soil, and, in turn, reduces their uptake by plants (del Real et al, 2013). The Cr stress-induced decrease in root length in the present study could be because of Cr accumulation in root cells or due to damage of root tip cells, whereas the decrease in shoot length may be due to ultrastructural damage in leaf mesophyll cells, which ultimately results in decreased shoot development.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, adverse effects of Cr on plant growth and biomass and chlorophyll contents have also been reported in mung bean plants(Rout et al 1997; Bera et al 1999; Samantary 2002; Banerjee et al 2008;Suthar et al 2014). This decrease in plant growth and biomass might be due to increase in metal uptake and decrease in nutrient uptake by the plants under metal stress(Rizwan et al 2012;Pradas-del-Real et al 2013;Keller et al 2015;Khaliq et al 2015). Under Cr stress, reduction in photosynthetic pigments might be due to structural alterations of chloroplast and/or inhibition of gas exchange attributes(Ali et al 2011;Rodriguez et al 2012;Gill et al 2015).…”
mentioning
confidence: 88%
“…It is toxic to most plants and is detrimental to their growth, they do not possess specific uptake mechanisms in plants unlike essential metals (Shanker et al, 2005). The uptake of Cr (III) in plants is not affected by metabolic inhibitor and research has shown that the rate of uptake of Cr (VI) in plants is higher than that of Cr (III) (Pradas-del-Real et al, 2013). This is because Cr (VI) can easily cross the cell membrane and can be transported with phosphate-sulphate carriers.…”
Section: Ibezim-ezeani Mu; Ihunwo Ocmentioning
confidence: 99%